SMARCA4 deficiency in small cell lung cancer: A case report and narrative review of the literature - Andreas M. Matthaiou; Ioannis Tomos; Nikoleta Bizymi; Ioannis Vamvakaris; Nektarios Anagnostopoulos; Aikaterini Papadopoulou; Kalliopi Angelou; Grigoris Stratakos; Adamantia Liapikou (Biomolecules & Biomedicine)
SWItch/Sucrose Non-Fermentable (SWI/SNF) is a large protein complex with a central role in chromatin remodeling and genome transcription. The catalytic subunits of the SWI/SNF related BAF chromatin remodeling complex subunit ATPase 2 (SWI/SNF SMARCA2; also called BRM) and SWI/SNF related BAF chromatin remodeling complex subunit ATPase 4 (SMARCA4; also called BRG1) are encoded by the SMARCA2 and SMARCA4 genes, respectively, and are mutually exclusive. Loss of either SMARCA2 and/or SMARCA4 has been previously reported in several types of malignant solid tumors of the gastrointestinal and genitourinary tract. So far, their absence in non-small cell lung cancer has been observed in a series of studies involving primary tumors and cell lines, where it is associated with loss of differentiation and heightened tumorigenic potential leading to an unfavorable prognosis. SMARCA2 and SMARCA4 deficiency is frequent in solid predominant adenocarcinomas and tumors with low levels of bronchial epithelial markers, including thyroid transcription factor 1. A rare case of SMARCA4 deficiency in small cell lung cancer is described. A 57-year-old male patient, with no medical history of past illness, was admitted to our center for the investigation and management of a space-occupying lesion in the right upper lung lobe with tracheal and mediastinal infiltration. Biopsy of a lymph node in the right supraclavicular region was diagnostic for small cell lung cancer with regional loss of SMARCA4. The patient demonstrated progressive respiratory failure and clinical deterioration and eventually deceased despite intubation and transfer to the intensive care unit. This case indicates that SMARCA4-deficient small cell lung cancer may present with an aggressively deteriorating phenotype with poor outcomes for the patie